A Proposed Mechanistic and Translational Framework for Assessing Reproductive Toxicity of Hexavalent Chromium (Cr(VI)) - Neamah, Asmaa M. (American Journal of Biology and Natural Sciences, 2026)
Cr(VI) is a highly mobile and a very powerful environmental toxicant, which is well-known to be Multi-organ toxic and globally spread. There are growing reasons to suspect that Cr(VI) has profound effects on the reproductive health of men and women, but existing evaluations are still disjointed on human epidemiological observations, animal research and mechanistic research. This research paper suggests a mechanistic-translational paradigm to be used in standardized assessment of Cr(VI)-induced reproductive toxicity. According to this work, regular marshaling of evidence provided by occupational and environmental human exposure research with controlled in vivo and in vitro research study yields consistent reproductive endpoints, dose-response relationships, and common pathways. In all the exposure models, Cr(VI) is always linked with poor sperm quality, hormonal interference, ovarian impairment, adverse pregnancy, and developmental toxicity. These actions all converge mechanistically upon oxidative stress generation, DNA damage, mitochondrial dysfunction, apoptosis, and interference with endocrine systems. Notably, Human and animal data can be aligned to allow the development of causal plausibility as well as enhance the reliability of risk assessment. To expand on this cross-model synthesis, we suggest a systematic evaluation plan, which is a combination of molecular biomarkers, functional reproductive outcomes, and developmental outcomes into a single evaluation plan. The framework will help to improve detection at the early stage, the decision-making process by regulators, and facilitate the elaboration of specific prevention and remediation plans. The offered model offers a scientifically sound basis in the process of developing an environmental reproductive risk assessment of Cr(VI) and the corresponding metal toxicants.